2010
DOI: 10.4067/s0716-97602010000100011
|View full text |Cite
|
Sign up to set email alerts
|

Effects of plant growth promoting rhizobacteria (PGPR) on rooting and root growth of kiwifruit (Actinidia deliciosa) stem cuttings

Abstract: The effects of plant growth promoting rhizobacteria (PGPR) on the rooting and root growth of semi-hardwood and hardwood kiwifruit stem cuttings were investigated. The PGPR used were Bacillus RC23, Paenibacillus polymyxa RC05, Bacillus subtilis OSU142, Bacillus RC03, Comamonas acidovorans RC41, Bacillus megaterium RC01 and Bacillus simplex RC19. All the bacteria showed indole-3-acetic acid (IAA) producing capacity. Among the PGPR used, the highest rooting ratios were obtained at 47.50% for semi-hardwood stem cu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
66
1
9

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
3
2

Relationship

1
9

Authors

Journals

citations
Cited by 150 publications
(85 citation statements)
references
References 23 publications
9
66
1
9
Order By: Relevance
“…Mert and Erturk (2017) reported the crude fat amount chestnut cultivars ranged from 0.87 to 2.61%. Our results are in accordance with those obtained by Erturk et al (2006) for C. sativa and hybrid cultivars, for Italian cultivars (Sacchetti and Pinnavaia, 2005) and for Spanish cultivars (De La Montana Miguelez et al, 2004 andPereiraLorenzo et al, 2006) Previous studies indicated cultivar/genotype differences on chemical content of fruit species, including stone fruits, nuts, berries and subtropical fruits (Celik et al, 2007;Ercisli, 2009;Ercisli et al, 2010;Erturk et al, 2010;Saridas et al, 2016;Yazici and Sahin, 2016;Zorenc et al, 2016).…”
Section: Proximate Compositionsupporting
confidence: 81%
“…Mert and Erturk (2017) reported the crude fat amount chestnut cultivars ranged from 0.87 to 2.61%. Our results are in accordance with those obtained by Erturk et al (2006) for C. sativa and hybrid cultivars, for Italian cultivars (Sacchetti and Pinnavaia, 2005) and for Spanish cultivars (De La Montana Miguelez et al, 2004 andPereiraLorenzo et al, 2006) Previous studies indicated cultivar/genotype differences on chemical content of fruit species, including stone fruits, nuts, berries and subtropical fruits (Celik et al, 2007;Ercisli, 2009;Ercisli et al, 2010;Erturk et al, 2010;Saridas et al, 2016;Yazici and Sahin, 2016;Zorenc et al, 2016).…”
Section: Proximate Compositionsupporting
confidence: 81%
“…PGPR induced root growth may be attributed to production of Indole 3-Acetic Acid (IAA) and IAA had long been known for its stimulatory effects on root proliferation (Barazani and Friedman 1999). Erturk et al (2010) reported 47% increase in rooting ratio when plants were inoculated with PGPR strains. Gamalero et al (2004) reported the promontory effects of fluorescent pseudomonads and an arbuscular mycorrhizal fungus on the growth and root parameters of tomato plant.…”
Section: Discussionmentioning
confidence: 99%
“…It includes the preparation of plant and animal products for people to use and their distribution to markets. Agriculture not only provides food and raw material but also employment opportunities to a very large proportion of the population (Sahin et al, 2002;Erturk et al, 2010;Cucci et al, 2016;Sorkheh and Khaleghi, 2016).…”
Section: Introductionmentioning
confidence: 99%